2014
DOI: 10.15237/gida.gd14023
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Enterocin B Producer Enterococcus Faecalis Mye58 Strain Isolated From Raw Milk

Abstract: Özet SAFETY EVALUATION OF ENTEROCIN B PRODUCER ENTEROCOCCUS FAECALIS MYE58 STRAIN ISOLATED FROM RAW MILK AbstractIn this study, we investigated the occurrence of enterocin, virulence factor and vancomycin resistance genes in bacteriocin producer Enterococcus faecalis MYE58 isolated from raw milk. We also tested hemolytic activity, gelatinase production and antibiotic resistance of this strain. It was determined that MYE58 strain inhibited Gram-positive bacteria, such as Listeria monocytogenes, Bacillus cereus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
3
3
0
1
Order By: Relevance
“…MCC0200 demonstrated remarkable tolerance to SIF for up to 360 min (Table S2), exhibiting a viable count of 1.1 ± 0.28 × 10 7 CFU/mL with only 1 log reduction in viability, suggesting the strain's robustness to survive in bile stress prevalent in GI tract. Our findings were in congruence with the reported literature, wherein, different studies have reported efficient bile tolerance (up to 1% and in some cases even up to 2%) trait of S. thermophilus [2,49,50].…”
Section: Assessment Of Probiotic Properties 331 Resistance To Gastric...supporting
confidence: 93%
See 1 more Smart Citation
“…MCC0200 demonstrated remarkable tolerance to SIF for up to 360 min (Table S2), exhibiting a viable count of 1.1 ± 0.28 × 10 7 CFU/mL with only 1 log reduction in viability, suggesting the strain's robustness to survive in bile stress prevalent in GI tract. Our findings were in congruence with the reported literature, wherein, different studies have reported efficient bile tolerance (up to 1% and in some cases even up to 2%) trait of S. thermophilus [2,49,50].…”
Section: Assessment Of Probiotic Properties 331 Resistance To Gastric...supporting
confidence: 93%
“…A study by Taj et al, 2022 [59], has reported auto-aggregation percentages of 97.8 ± 0.4, 61.2± 1.0, and 53.6 ± 0.6 for different strains of S. thermophilus. Tuncer and Tuncer (2014) [49] reported 49.55 ± Figure 2. Adherence of S. thermophilus MCC0200 to the hydrocarbons: chloroform, ethyl acetate and xylene (the BATH method was employed to measure the hydrophobicity of the cell surface of MCC0222.…”
Section: Aggregation Ability Of Mcc0200mentioning
confidence: 92%
“…Many research reports on cell auto-aggregation have been documented for the screening of LAB including probiotic bacteria. Tuncer and Tuncer, (2014) have reported that the autoaggregation value of S. thermophilus ST8.01 was recorded as 49.55 ± 6.24% which can be comparable with this study and even better results have been shown by the ST 144 and LB 144. Tamara et al, (2012) have also reported that three strains of L. plantarum possessed the ability to auto-aggregation and coaggregation, which are an important feature in the selection of probiotic bacteria.…”
Section: Cell Auto-aggregationsupporting
confidence: 89%
“…[1][2][3] Many types of adsorbents have been developed and tested for the recovery of uranium from seawater and aqueous media. To recover uranium from seawater at the price competitive with those from conventional uranium resources, many methods such as solvent extraction [4][5][6][7] ion exchange [8], flotation [9], biomass collection and adsorption [10][11][12][13][14] have been developed. The studies indicate that poly(acrylamidoximes) are the most promising candidate adsorbents for the recovery of uranium from seawater.…”
Section: Introductionmentioning
confidence: 99%